Counseling and Monitoring of Unemployed Workers: Theory and Evidence from a Controlled Social Experiment - Gerard J. van den Berg; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2001)
We investigate the effect of counseling and monitoring on the individual transition rate to employment. We theoretically analyze these policies in a job search model with two search channels and endogenous search effort. In the empirical analysis we use unique administrative and survey data concerning a social experiment with full randomization and compliance. The results show that counseling and monitoring do not affect the exit rate to work. Monitoring causes a shift from informal to formal job search. We combine our empirical results to the results from our theoretical analysis and the existing empirical literature, to establish a comprehensive analysis of the effectiveness of these policies.
Keywords: J65; J64; J58; 330; Unemployment duration; search effort; active labor market policy; treatment; search channels; multi-tasking; randomized social experiment; Arbeitsvermittlung; Arbeitsuche; Kontrolle; Experiment; Schätzung; Beschäftigungseffekt; Arbeitsmarktpolitik; Theorie; Niederlande